Efficient optimization and development of two methods for the determination of acrylamide in deep‐frying oil by liquid chromatography–tandem mass spectrometry: Application of multifactor analysis assessment strategy. Issue 3 (4th December 2022) - Zhang, Yanxia; Zhao, Huinan; Sun, Shanshan; Lu, Lanxiang; Xue, Xia; Su, Shufang; Gong, Pixue; Zheng, Wenjing; Wang, Mingdong; Wang, Jun; Zhu, Jianhua; Liu, Yanming; et al.
Abstract : A new multifactor analysis assessment strategy was developed for evaluating, optimizing, and comparing analytical techniques for acrylamide in frying oils. Based on five indices (absolute recovery, absolute matrix effect, the intensity of the full ion scan, and the precursor ion scan to m / z 184 and m / z 241), the proposed strategy was performed with radar analysis, relative contribution analysis, and the entropy‐weighted technique for order performance by similarity to ideal solution analysis. Two novel methods based on quick, easy, cheap, effective, rugged, and safe extraction methodology and gel permeation chromatography–liquid–liquid extraction followed by liquid chromatography–tandem mass spectrometry have been developed for the analysis of acrylamide in frying oils. Two methods were suitable for rapid and sensitive analysis of acrylamide in oils in different laboratories, with a limit of quantitation at 2 μg/kg, and the average recovery ranging from 92.5% to 107.8%, with relative standard deviations below 10%. When considering automation efficiency and matrix effects, gel permeation chromatography is the most efficient method, whereas the other method has an advantage when analyzing large samples. The developed methods were used in a pilot study to analyze frying oils with acrylamide content below 9.82 μg/kg, showing that the repeated frying process did not produce significant content of acrylamide in oils.